Evaluation of magnetic resonance thermometry performance during MR-guided hyperthermia treatment of soft-tissue sarcomas in the lower extremities and pelvis - Spyridon N. Karkavitsas; Marianne Göger-Neff; Maria Kawula; Kemal Sumser; Benjamin Zilles; Martin Wadepohl; Guillaume Landry; Christopher Kurz; Wolfgang G. Kunz; Olaf Dietrich; Lars H. Lindner; Margarethus M. Paulides (International Journal of Hyperthermia)
Introduction This study evaluated the performance of magnetic resonance thermometry (MRT) during deep-regional hyperthermia (HT) in pelvic and lower-extremity soft-tissue sarcomas.Materials and methods 17 pelvic (45 treatments) and 16 lower-extremity (42 treatments) patients underwent standard regional HT and chemotherapy. Pairs of double-echo gradient-echo scans were acquired during the MR protocol 1.4 s apart. For each pair, precision was quantified using phase data from both echoes (‘dual-echo’) or only one (‘single-echo’) in- or excluding body fat pixels in the field drift correction region of interest. The precision of each method was compared to that of the MRT approach using a built-in clinical software tool (SigmaVision). Accuracy was assessed in three lower-extremity patients (six treatments) using interstitial temperature probes. The Jaccard coefficient quantified pretreatment motion; receiver operating characteristic analysis assessed its predictability for acceptable precision (<1 °C) during HT.Results Compared to the built-in dual-echo approach, single-echo thermometry improved the mean temporal precision from 1.32 ± 0.40 °C to 1.07 ± 0.34 °C (pelvis) and from 0.99 ± 0.28 °C to 0.76 ± 0.23 °C (lower extremities). With body fat-based field drift correction, single-echo mean accuracy improved from 1.4 °C to 1.0 °C. Pretreatment bulk motion provided excellent precision prediction with an area under the curve of 0.80–0.86 (pelvis) and 0.81–0.83 (lower extremities), compared to gastrointestinal air motion (0.52–0.58).Conclusion Single-echo MRT exhibited better precision than dual-echo MRT. Body fat-based field-drift correction significantly improved MRT accuracy. Pretreatment bulk motion showed improved prediction of acceptable MRT temporal precision over gastrointestinal air motion.